1993
DOI: 10.1161/01.str.24.7.976
|View full text |Cite
|
Sign up to set email alerts
|

Major depression in stroke patients. A 3-year longitudinal study.

Abstract: Background and Purpose: This prospective study was designed to examine the contributions of neurobiological, functional, and psychosocial factors to major depression after stroke. In addition, the prevalence and longitudinal course of major depression were studied.Methods: Major depression, functional ability, and social network were assessed repeatedly for a period of 3 years in a population-based cohort of 80 patients with acute stroke (mean age, 73 years). Cerebral atrophy and brain lesion parameters were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
448
5
47

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(536 citation statements)
references
References 40 publications
36
448
5
47
Order By: Relevance
“…In subsequent studies, Starkstein et al, 4 Astrom et al, 5 Morris et al, 6 Herrmann et al, 7,8 Vataja et al, 9,10 all found significant associations between left frontal and/or left basal ganglia lesions and major poststroke depression. Furthermore, Bolla-Wilson et al 11 and Spalletta et al 12 found an association between major depression in patients with left hemisphere stroke and cognitive impairment, while Spalletta 13,14 found an association between unawareness of emotions and right hemisphere stroke.…”
Section: Introductionmentioning
confidence: 94%
“…In subsequent studies, Starkstein et al, 4 Astrom et al, 5 Morris et al, 6 Herrmann et al, 7,8 Vataja et al, 9,10 all found significant associations between left frontal and/or left basal ganglia lesions and major poststroke depression. Furthermore, Bolla-Wilson et al 11 and Spalletta et al 12 found an association between major depression in patients with left hemisphere stroke and cognitive impairment, while Spalletta 13,14 found an association between unawareness of emotions and right hemisphere stroke.…”
Section: Introductionmentioning
confidence: 94%
“…Estimates from individual studies assessing major depression meeting DSM criteria varied across studies from 2% during admission 15 in one cohort to 31% at three months in a different cohort. 16 In the latter cohort, major depression meeting DSM criteria was assessed over three years. Estimates were 31% at three months, 16% at 1 year, 19% at 2 and 29% at three years after stroke (only 50 participants remained in the final cohort).…”
Section: Depressionmentioning
confidence: 99%
“…Estimates were 31% at three months, 16% at 1 year, 19% at 2 and 29% at three years after stroke (only 50 participants remained in the final cohort). 16 Population based stroke registers with long-term follow-up [17][18][19] demonstrate that depression after stroke is a chronic relapsing disorder. Of people with depression at the first assessment, between 13% 18 and 52% 19 still had depression at a year.…”
Section: Depressionmentioning
confidence: 99%
“…In its initial phase, depression is usually related to biological changes, but depression that occurs later is often related to social functions (Robinson 2003). Therefore, emotional disorders such as depression and anxiety that appear after stroke must be dealt with effectively to help with rehabilitation (Aström et al 1993). Literature treatment is an auxiliary tool that treats neurosis as well as emotional or behavioral disorders; thus, it might be an effective therapy method for PSD as well (Jacobs and Mosco 2011;Eum et al 2014).…”
Section: Literature Therapy For Stroke Patientsmentioning
confidence: 99%